Increasing The Quality of Teacher's Pedagogic Competence to Develop Student Learning Motivation - I Nengah Karsana; Ni Made Suyeni; Heny Perbowosari (Jurnal Penjaminan Mutu, 2020)
This study aims for teacher pedagogical competence in planning the learning, learning processes, and increasing student motivation. To achieve this goal, this study used a qualitative approach. Data collection techniques were done through interviews, observation, and documentation study. Data analysis procedures were data reduction, data display, and verification. While the research subjects were the principal, vice-principal, and teacher. The results showed that: (1) Teacher's pedagogical competence in planning the learning was done by making a draft lesson plan, but some teachers do not carry lesson plans during the teaching and learning process so that learning objectives are not achieved optimally; (2) Teacher's pedagogical competence in the learning process was carried out by exploring and strengthening several learning materials as contained in the textbook, while in the learning process there is poor classroom management and less disciplined use of time; and (3) Teacher pedagogical competence in increasing student learning motivation was done by giving opportunities to students to be actively involved in using information and communication technology facilities in achieving learning objectives, communicating effectively with students, and taking reflective actions to improve the quality of learning.